THE USE OF HELLOTALK APPLICATION IN LEARNING STUDENTS SPEAKING SKILLS AT JUNIOR HIGH SCHOOL - Syaharani, Namira; Santoso, Didik (TELL - US JOURNAL, 2025)
The aim of this research is to describe the effect of hellotalk application in learning speaking skills. This research used is a quasiexperiment research with belong to postest only design. The population of this study consisted of sixty respondents of Junior High School students, which is the largest number of respondents for two group. Thirty for the experimental group and thirty for the control group, while the sample was taken by using cluster random sampling. Data analysis was carried out using the t test. The instrument of this research is a speaking test. The t observed = 18.29 is greater than the t table = 2.00. This means that the research hypothesis is accepted while the null hypothesis is rejected. This shows that the hellotalk application is effective in learning speaking skills